Progress in Corrosion Science and Engineering II - Pyun, Su-Il.; Lee, Jong-Won.; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Topics in Number 47 include: Advances in the study of electrochemical and corrosion phenomena in high subcritical and supercritical aqueous solutions Passive oxide films on iron by in-situ detection of optical techniques Probing and modeling of galvanic coupling phenomena in localized corrosion Preparation of hierarchical (nano/meso/macro) porous structures using electrochemical deposition From reviews of previous volumes: "This long-standing series continues its tradition of offering high quality reviews of established and emerging subject areas, together with the less common aspects of electrochemical science... [and]... deserves a place in electrochemistry libraries and should prove useful to electrochemists and related workers." $1 (BChemistry and Industry "Continues the valuable service that has been rendered by the Modern Aspects series." $1 (BJournal of Electroanalytical Chemistry "Will definitely be of much use to researchers in the field of electrochemistry. . . . The editors of this well-produced volume deserve all appreciation for maintaining the excellent standard of the series." $1 (BBulletin of Electrochemistry "Extremely well-referenced and very readable.... Maintains the overall high standards of the series." $1 (BJournal of the American Chemical Society.s
Advances in the Study of Electrochemical and Corrosion Phenomena in High Subcritical and in Supercritical Aqueous Solutions -- Passive oxide films on iron by in-situ detection of optical techniques -- Probing and modelling of galvanic coupling phenomena in localized corrosion -- Preparation of Hierarchical (nano/meso/macro) Porous Structures using electrochemical deposition.
Keywords: Chemistry; Electrochemistry; Tribology; Corrosion and anti-corrosives.; Coatings; Chemistry; Electrochemistry; Tribology, Corrosion and Coatings; Electronic books